THE CORRELATION BETWEEN EFL LEARNERS’ MOTIVATION ON ENGLISH COURSE AND THEIR ENGLISH LEARNING ACHIEVEMENT - Apriliyanti, Dewi Listia (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
Abstract A Study has been conducted to examine the correlation between EFL learners’ motivation on English course (X) and their English learning achievement (Y). A mixed method design used in this study. Instruments of this research were observation, questionnaire, document, and interview. Quantitative method used to measure the correlation between two variables. 30 higher students of the public school have involved in this study. The result showed that the correlation between EFL learners’ motivation on English course and their English score. Even though the correlation was positive, but it was low and not significant. Meanwhile, The investigation found five explanations. First, in some cases, the method that teacher used for learning activity was not suitable with the students’ condition. Second, most students felt difficulty with grammatical structure. Third, students would understand the material if they felt interesting with their teacher and materials. If they didn’t feel comfortable with both of those things, they would not understand the material at all. Forth, they didn’t have high curiosity because they were not remembered about the material explanation from their tutor on English course in the next day. It means that they were not learned it again at home. Fifth, 43% of students would rather to studying with their teacher at school than at English course. 36% of students would rather to studying with their teacher at courses that at school because they felt more understand learning at English course and 21% of samples were abstained. Abstrak Penelitian ini dilakukan untuk menguji korelasi antara motivasi peserta didik bahasa Inggris sebagai bahasa asing (EFL) dalam mengikuti kursus bahasa Inggris (X) dan prestasi belajar bahasa Inggris mereka di sekolah (Y). Desain metode campuran digunakan dalam penelitian ini. Instrumen penelitian ini adalah observasi, kuesioner, dokumen, dan wawancara. Metode korelasi digunakan untuk mengukur hubungan antar dua variabel. 30 siswa Sekolah Menengah Atas (SMA) terlibat sebagai sampel dalam penelitian ini. Hasil penelitian menunjukan ada korelasi antara motivasi peserta didik EFL terhadap nilai bahasa Inggris mereka. Meskipun hasil menunjukan adanya hubungan yang positif namun rendah dan tidak signifikan. Hasil investigasi menemukan lima temuan. Pertama, dalam beberapa kasus, metode yang digunakan guru untuk kegatan belajar tidak sesuai dengan kondisi siswa. Kedua, kebanyakan siswa merasa kesulitan dalam memahami stuktur gramatika dalam bahasa Inggris. Ketiga, siswa akan memahami materi jika mereka merasa tertarik dengan guru dan bahan ajarnya. Jika mereka tidak merasa nyaman dengan kedua hal tersebut, merek tidak akan memahami materi sama sekali. Keempat, mereka tidak memiliki keingintahuan yang tinggi karena mereka tidak ingat penjelasan materi dari tutor mereka pada saat kursus bahasa inggris dihari berikutnya. Artinya mereka tidak mempelajarinya lagi dirumah. Kelima, 43% siswa memilih untuk belajar dengan guru mereka disekolah, 36% siswa memilih belajar dengan tutor di tempat kursus mereka, dan 21% tidak memilih keduanya. How to Cite : Apriliyanti, D. L., Darliani. Y. (2017). The Correlation Between EFL Learners’ Motivation on English Course and Their English Learning Achievement. TARBIYA: Journal of Education in Muslim Society, 4(2), 232-239. doi:10.15408/tjems.v4i2.6401. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i1.6401